Global Trends in Reproductive Health Education Among High School Students: A Systematic Review - Hasnah, Andi; Akib, Irwan; Yaumi, Muhammad (PPSDP International Journal of Education, 2025)
This systematic review and bibliometric analysis maps global research trends in reproductive health education (RHE) among high school students from 2015 to 2025. Data from 447 Scopus-indexed publications were analyzed using VOSviewer and Biblioshiny. Findings reveal a steady increase in publications, peaking in 2022, with significant contributions from China, Indonesia, and Ethiopia. Thematic analysis identified four dominant domains: adolescent behavior, school-based education, gender and rights, and policy innovation, indicating a shift from risk prevention toward empowerment-oriented and technology-based education. The study's novelty lies in its decade-long global synthesis, integrating bibliometric and systematic approaches. The findings underscore the need for inclusive, culturally sensitive, and digitally-enhanced curricula to inform evidence-based policymaking aligned with the Sustainable Development Goals (SDGs).